2007
DOI: 10.1590/s0101-31222007000200028
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência do fungicida carboxin + thiram no tratamento de sementes de amendoim

Abstract: RESUMO -O tratamento de sementes com fungicida é um seguro de baixo custo para os produtores de sementes e plantadores de amendoim. O uso de fungicidas adequados pode contribuir para o melhor desempenho do material de propagação, proporcionando maiores rendimentos na colheita. Esta pesquisa teve por objetivo avaliar a eficiência do fungicida carboxin + thiram e a viabilidade do uso de óleo vegetal e de surfactante à base de organosilicone como agentes veiculadores do fungicida, no controle de fungos associados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 5 publications
1
5
0
8
Order By: Relevance
“…However, the germination rate of the seeds in the test of seedling emergence in sand was higher than it was in the germination test. These results are consistent with other studies performed with peanut (Bittencourt et al 2007) and soybean seeds (Schuab et al 2006). The humidity and temperature conditions in the germination test and the proximity between seeds on the toweling rolls may create a favorable "microclimate" for the proliferation of several microorganisms, thus negatively affecting seed germination.…”
Section: Resultssupporting
confidence: 94%
“…However, the germination rate of the seeds in the test of seedling emergence in sand was higher than it was in the germination test. These results are consistent with other studies performed with peanut (Bittencourt et al 2007) and soybean seeds (Schuab et al 2006). The humidity and temperature conditions in the germination test and the proximity between seeds on the toweling rolls may create a favorable "microclimate" for the proliferation of several microorganisms, thus negatively affecting seed germination.…”
Section: Resultssupporting
confidence: 94%
“…As to Carboxin + Thiram doses, there were no differences for all traits (Table 2), both by analysis of variance (F test) and by Tukey test, and both at 5% probability, which demonstrates that fungicide did not affect the seed quality, regardless of lot. Bittencourt et al (2007) found no phytotoxic effect of this fungicide on peanut seed, and observed a greater emergence of treated seeds against the untreated control, because the fungicides reduced the incidence of "damping-off" caused by fungi in seeds and in the soil. Similar results were reported by Arsego et al (2006) and Lobo (2008) with rice, and by Tropaldi et al (2010) and Santos et al (2012) with castor seed treated with this fungicide.…”
Section: Resultsmentioning
confidence: 85%
“…There are studies assessing the effects of this fungicide on seed physiological quality of cotton (Faria et al, 2003), castor plant (Tropaldi et al, 2010;Santos et al, 2012), peanuts (Bittencourt et al, 2007), rice (Schuch et al, 2006;Lobo, 2008;Morales et al, 2012), maize (Fessel et al, 2003), safflower , and wheat (Marini et al, 2011), among other species. However, no research on vegetables was found that studied the fungicide effect on seed quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Bittencourt et al (2007), fungicides (carboxin + thiram) provides greater protection to the seed, against the microorganisms present in the soil and the seed itself, especially when exposed to unfavorable conditions for their development, and also during storage. Means followed by the same upper case letter in line and lower case in column do not differ according to Tukey test at 5% probability.…”
Section: Resultsmentioning
confidence: 99%